51-x=36

Simple and best practice solution for 51-x=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 51-x=36 equation:


Simplifying
51 + -1x = 36

Solving
51 + -1x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-51' to each side of the equation.
51 + -51 + -1x = 36 + -51

Combine like terms: 51 + -51 = 0
0 + -1x = 36 + -51
-1x = 36 + -51

Combine like terms: 36 + -51 = -15
-1x = -15

Divide each side by '-1'.
x = 15

Simplifying
x = 15

See similar equations:

| 14k(8-k+h)= | | 40c+120a=500 | | 5m-2=4+m | | -x-111+10x=33 | | -5x-6y-6x+7y= | | -5x-6y-6x+7= | | (7u^3-u^2-7)+(2u^3-4u^2)= | | 18x-8=-24 | | 0.80x=94 | | -3x^2+600x-3375=0 | | .50x+3+.80=1.80 | | 3b+1+b=2b+9 | | 3(y+2)=y+14 | | -9x-101-3x=79 | | 8x^2y+-5yx^2= | | 0.02x=5 | | x^2-200x+1125=0 | | (-a+5c)+(-7a+2c+3)= | | w+5.3=10.1 | | 25b+15= | | 7+(6x-5)4-30x= | | 9.2x-1.6x=28 | | -6+3x-22=23 | | 3(p+5)-8+11p= | | n-3n+8=5+n | | (2y^2+9y+4)+(-3y^2-3y-9)= | | x+4-7=24 | | xv-w=6 | | -3x+18=12 | | 7x+0.5y=-2 | | -8x-x=18 | | 2x-8=2+5x |

Equations solver categories